2001
DOI: 10.1080/3054980020030637
|View full text |Cite
|
Sign up to set email alerts
|

Education for all - in whose language?

Abstract: In the rst part of this article the question of the language of instruction is seen in relation to questions of poverty, power and partnership. In the second part the fate of the African languages in some selected countries is given a closer look. Two distinct trends are noted, one strengthening the dominant languages which, in the context of Africa, means the former colonial languages and one focusing on a growing concern for a preservation and revival of African languages as languages of instruction in at le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 9 publications
0
19
0
Order By: Relevance
“…English-only instruction and monoglossic language policies have yielded relatively lower educational achievement for rural students, in part because they rarely have an opportunity to use English outside of the classroom (Brock-Utne 2001;Muthwii 2004). Studies in several multilingual settings have shown similar deficit ideologies towards multilingual learners and their home languages (see, for example, Heller 1999;Lin 1996;Makoe and McKinney 2014;McKinney et al 2015;Smith 2001).…”
Section: Introductionmentioning
confidence: 99%
“…English-only instruction and monoglossic language policies have yielded relatively lower educational achievement for rural students, in part because they rarely have an opportunity to use English outside of the classroom (Brock-Utne 2001;Muthwii 2004). Studies in several multilingual settings have shown similar deficit ideologies towards multilingual learners and their home languages (see, for example, Heller 1999;Lin 1996;Makoe and McKinney 2014;McKinney et al 2015;Smith 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Plans existed to have Kiswahili as the language of instruction in secondary school and the universities (Brock-Utne, 2002). A detailed historical narration of the language policy of Tanzanian education is well illustrated in previous literature (Brock-Utne, 1993;2000:2001a2001b).…”
Section: Background Of a Swahili Language And Historical Context Of Tmentioning
confidence: 97%
“…On the one hand, there are confi dent assertions that the global spread of English is natural, neutral and benefi cial (Brutt-Griffl er 2002 ;Crystal 1997b ;Graddol 2006 ) while on the other hand are claims that it is detrimental in that it brings about social stratifi cation, exclusion and new problems associated with education, literacy and language rights (Bamgbose 2000 ;Brock-Utne 2001 ;Phillipson 1992 ;Phillipson and Skutnabb-Kangas 1996 ;Skutnabb-Kangas 2000 ;Skutnabb-Kangas and Phillipson 1995 ). These established groups of views refl ect scholars' different approaches to the study of language ideologies.…”
Section: English Language Ideologies In a Globalising Worldmentioning
confidence: 99%
“…They view the linguistic phenomenon as 'natural, neutral and benefi cial'. Still others allege its detrimental effects of global English, especially in the context of Outer Circle countries, where English is largely acquired through formal education (Bamgbose 2000 ;Brock-Utne 2001 ). They assert that English brings about social stratifi cation, exclusion and problems associated with education, literacy and language rights.…”
Section: Different Types Of Ideologies Of "Global English"mentioning
confidence: 99%